PS-C36-9: A REVIEW OF THE PHARMACOKINETIC PROFILES OF THE 40 MOST COMMONLY PRESCRIBED CARDIOMETABOLIC MEDICATIONS. (January 2023) - Salim, Farah; Osman, Hanad; Alghamdi, Randah; Lane, Dan; Bernieh, Dennis; Jones, Donald; Gupta, Pankaj
Abstract : Objective: To collate the pharmacokinetic (PK) parameters of the 40 most commonly prescribed cardiometabolic medications from published literature to provide a useful reference source for clinicians when interpreting results of chemical adherence testing. Design and Methods: Non-adherence to medication is a prime cause of treatment failure and costs the UK health system approximately £500 million annually. A recent meta-analysis on adherence to 7 cardiovascular drug classes revealed a non-adherence rate of 43%. Chemical adherence testing (CAT) by liquid chromatography tandem mass spectrometry (LC-MS/MS) is an objective method for testing patient adherence to medication and has been proven to be effective in managing disease progression. To improve result interpretation, factors including dose time, sample collection, and PK need to be better understood. The list of the most commonly prescribed drugs was obtained using the NHS Prescription Cost Analysis 2020/2021. Data on the pharmacokinetic parameters was collected from original papers from the following sources: Lexicomp: Medical Library Goodmans & Gilmans: The pharmacological basis of therapeutics, 13th edition Clarks analysis of drugs and poisons 4th edition Martindale: The complete drug reference All original manuscripts were reviewed, filtered and graded, following a robust criteria. The collected PK parameters focused on the bioavailability, volume of distribution, peak concentration, minimum plasma concentration, time to peak concentration, half-life, clearance and urine excretion. Results: A total of 3004 papers were initially screened for pharmacokinetic data, of which, 274 papers were relevant. These papers were further filtered, a total 84 papers adhered to the criteria for grading. Propranolol was one of the most prescribed cardiometabolic drugs with 6, 124, 180 prescriptions issued in the UK between 2020–2021. The half-life for Propranolol 80 mg (3.5 h), the peak time (1.5 h), the peak concentration (49 ± 8 ng/mL). Edoxaban was prescribed 1, 584, 638 times in the time period selected. Mean PK parameters for steady state levels of Edoxaban were: bioavailability (99.7%), urine excretion (44.7 ± 14.8%), clearance (535 ± 15.5 mL/min), volume of distribution (426 ± 30.7 L), half-life (9.2 ± 30.5 h), peak time (2 ± 1.03) and peak concentration (507 ± 17.3 ng/mL). Conclusions: This is one of the first studies to utilise a criteria for collecting and grading of PK parameters from published literature for common cardiometabolic medications. Medications have diverse pharmacokinetic profiles hence; systematic collection of these parameters will be a useful reference for clinicians when interpreting results of CAT for medication presence in patient samples.